Autoethnography as a Research Method in Cross-Cultural Education Studies - Tian, Xiaoming; Zhang, Zeyu; Xu, Lihua (Cross-Cultural Education Studies, 2025)
This review article examines the application of autoethnography as a research method and pedagogical tool within cross-cultural education studies. It argues that autoethnography’s unique epistemological grounding in personal experience, systematic reflexivity, and relational ethics provides a powerful means to investigate the complex and often unspoken affective dimensions of teaching and learning in cross-cultural education. The review synthesizes a diverse body of literature to demonstrate how autoethnography effectively bridges theoretical frameworks with lived educational practice. It traces the method’s intellectual genealogy and evolution, outlining its major typologies, including analytic, evocative, critical, and collaborative autoethnography, and their relevance for educational research. The analysis highlights autoethnography’s distinctive capacity to foster critical cultural awareness, challenge embedded power imbalances, and cultivate genuine empathy among educators and students, with specific illustrations from teacher education, foreign-language learning, and the communication of Chinese educational wisdom. However, the article also critically engages with significant challenges, including ongoing debates about methodological rigor, ethical complexities in representing self and others, and practical implementation barriers in diverse educational settings. The conclusion affirms that when practiced with analytical discipline and ethical responsibility, autoethnography offers a unique pathway for generating situated and transformative knowledge in cross-cultural education. By creating meaningful connections between personal narrative and broader cultural-structural analysis, it ultimately contributes to more nuanced understandings of cross-cultural educational encounters and their implications for educational theory and practice.